Microstructure Effects on Electrochemical Characteristics for Plasma Spray Deposited LiFePO4 Films - Satishkumar, B. C.; Zhou, Xuan; Moroz, Nick; Mohanty, Pravansu; Bi, Fu; Wang, Yaping (Journal of Coating Science and Technology, 2014)
The electrochemical behavior of composite electrodes used in Li ion batteries is influenced by factors such as microstructural characteristics (e.g. particle size, crystallinity, porosity etc.) and composition. For optimal performance of electrodes these factors are of utmost concern and serve as motivation for research in this field. In this report, we investigated LiFePO4 films synthesized by a novel plasma spray deposition method, which has capability for direct deposition of LiFePO4 films with carbon. This enables electrode characterizations to be carried out at the film level, without recourse to steps involving powder material handling. In this report microstructure and electrochemical properties of LiFePO4 films were investigated to elucidate their unique characteristics. Our studies show that factors such as porosity and microstructure of the films affect the electrochemical properties. The mechanical compression and thermal annealing experiments are shown to affect the electrochemical characteristics of LiFePO4 films. We show that annealing treatment leads to a drastic improvement in impedance and charge-discharge capacities for the LiFePO4 films. These treatments could serve to improve the electrode properties of porous film based materials for Li ion batteries and help us develop new film based materials for energy storage applications.